Should Culture Samples Be Taken During All Revision Total Ankle Arthroplasty (TAA)?. (July 2019) - Fuchs, Daniel
Recommendation: We recommend that intraoperative cultures be taken during revision total ankle arthroplasty (TAA). The result of intraoperative cultures should be interpreted together with clinical suspicion for infection and the results of the laboratory and imaging investigations. We also recommend that multiple tissue specimens be collected. Given a lack of evidence for routine intraoperative cultures for revision TAA literature, this recommendation is based on analogous evidence in the total hip and knee replacement literature. Level of Evidence: Consensus. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus)